2017
DOI: 10.1189/jlb.2mr0317-105r
|View full text |Cite
|
Sign up to set email alerts
|

Shp1 function in myeloid cells

Abstract: The mouse was first described in 1975 as a model of systemic inflammation and autoimmunity, as a result of immune system dysregulation. The phenotype was later ascribed to mutations in the cytoplasmic tyrosine phosphatase Shp1. This phosphatase is expressed widely throughout the hematopoietic system and has been shown to impact a multitude of cell signaling pathways. The determination of which cell types contribute to the different aspects of the phenotype caused by global Shp1 loss or mutation and which pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 186 publications
(246 reference statements)
1
74
0
1
Order By: Relevance
“…The protein tyrosine phosphatase Src homology region 2 domain-containing phosphatase-1 (Shp1) is a potential immunotherapeutic target ( 7 , 8 ). Shp1 is broadly expressed in the hematopoietic compartment and acts as a negative regulator of signaling in both innate and adaptive immune cells ( 9 , 10 ). Thus, alterations in Shp1 have the potential to impact an anti-tumor immune response in several different ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein tyrosine phosphatase Src homology region 2 domain-containing phosphatase-1 (Shp1) is a potential immunotherapeutic target ( 7 , 8 ). Shp1 is broadly expressed in the hematopoietic compartment and acts as a negative regulator of signaling in both innate and adaptive immune cells ( 9 , 10 ). Thus, alterations in Shp1 have the potential to impact an anti-tumor immune response in several different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Shp1 exerts its inhibitory signaling function by binding to phosphorylated immunoreceptor tyrosine-based inhibitory motifs (ITIMs) on a variety of immunoreceptors. Upon binding and activation, Shp1 dephosphorylates its substrates, thereby transducing inhibitory signals that restrict immune cell function ( 9 , 10 ). Consistent with this, mouse models with spontaneous mutations in the gene encoding Shp1, Ptpn6 , that affect its expression or function develop an inflammatory/autoimmune disease associated with hyperactivation of multiple types of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…27 SHP-1 contains two Src homology (SH)2 domains and a PTP domain and binds to immunoreceptor tyrosine-based inhibition motif-containing proteins, including FcRIIb, carcinoembryonic antigen cell adhesion molecule-1 (CD66a), and platelet and endothelial cell adhesion molecule-1 (CD31) to serve as negative regulator in multiple immune signaling pathways. 28 SHP-1 deficient mice (Ptpn6 me-v/me-v ) display spontaneous and severe inflammatory and autoimmune diseases, indicating that SHP-1 is a key regulator of immune cell function. Our previous results showed that SHP-1 suppresses NF-κB and MAPK signaling transduction in response to infection with enterohemorrhagic Escherichia coli by inhibiting K63-linked polyubiquitination of transforming growth factor beta-activated kinase 1.…”
Section: Introductionmentioning
confidence: 99%
“…SHP-1 is expressed by all mature haematopoietic lineages and at low levels (different isoforms) by endothelial cells [10,21]. SHP-1 consists of 3 domains; the N-terminal Src homology-2 (SH2) domain, the C-terminal SH2 domain, and the C-terminal catalytic PTP domain [22], and maximal phosphatase activity is achieved only when both SH2 domains are engaged.…”
Section: Shp-1 2 Pathways: Molecular Biologymentioning
confidence: 99%
“…Although a PTP was traditionally thought to inactivate kinases and to serve as a negative regulator of cell functions, SHP-1, 2 have been shown to promote cell growth and act by both upregulating positive signaling pathways [8] and by downregulating negative signaling pathways [9]. SHP-1 is expressed widely throughout the haematopoietic system and has been shown to impact a multitude of cell signaling pathways [10]. In addition, SHP-2 contributes to the progression of a number of cancer types including leukaemias as well as gastric and breast cancers.…”
Section: Introductionmentioning
confidence: 99%